Comparison of Brain Activation Between Different Modes of Motor Acquisition: A Functional Near‐Infrared Study - Meng‐Hsuan Tsou; Pei‐Yun Chen; Yi‐Ting Hung; Yong‐Wei Lim; Shiuan‐Ling Huang; Yan‐Ci Liu (Brain and Behavior)
ABSTRACT Background Different modes of motor acquisition, including motor execution (ME), motor imagery (MI), action observation (AO), and mirror visual feedback (MVF), are often used when learning new motor behavior and in clinical rehabilitation. Purpose The aim of this study was to investigate differences in brain activation during different motor acquisition modes among healthy young adults. Methods This cross‐sectional study recruited 29 healthy young adults. Participants performed a functional reaching and grasping task under ME, MI, AO, and MVF mode with their right arms at a frequency of 0.5 Hz for 1 min per task. Each task was performed three times in a random order. Brain activation in the supplementary motor area (SMA), premotor cortices (PMC), and primary motor cortices (M1) during tasks was measured using functional near‐infrared spectroscopy through 16 source‐detector channels. Results ME showed significant activation in bilateral PMC, M1, and right SMA, with higher activation in the contralateral M1. MI induced greater activity in the PMC and SMA, particularly in the ipsilateral regions. MVF resulted in significant activation in bilateral PMC, SMA, and M1. AO showed an increasing trend in brain activation, but no significant differences in any channels. Compared to AO, ME and MVF induced significantly greater brain activity in M1. Conclusion Activation levels under MI and MVF were comparable to that of ME. MI and MVF induced greater activity in the PMC and SMA, and MVF showed significant activity in all brain areas, especially in the bilateral M1. These findings support the application of different motor acquisition strategies according to individual needs. When ME cannot be executed, such as for individuals with hemiparesis or severe impairments of both upper extremities, MI and MVF may be applied, respectively, to drive neuroplastic changes.